A mucin-type O-glycosyltransferase modulates cell adhesion during Drosophila development. - Zhang, L.; Zhang, Y.; Hagen, K.G. (Journal of Biological Chemistry, 2008)
Cell-cell and cell-matrix adhesion are crucial during many stages of eukaryotic development. Here, we provide the first example that mucin-type O-linked glycosylation is involved in a developmentally regulated cell adhesion event in Drosophila melanogaster. Mutations in one member of the evolutionarily conserved family of enzymes that initiates O-linked glycosylation alter epithelial cell adhesion in the Drosophila wing blade. A transposon insertion mutation in pgant3 or RNA interference to pgant3 resulted in blistered wings, a phenotype characteristic of genes involved in integrin-mediated cell interactions. Expression of wild type pgant3 in the mutant background rescued the wing blistering phenotype, whereas expression of another family member (pgant35A) did not, revealing a unique requirement for pgant3. pgant3 mutants displayed reduced O-glycosylation along the basal surface of larval wing imaginal discs, which was restored with wild type pgant3 expression, suggesting that reduced glycosylation of basal proteins is responsible for disruption of adhesion in the adult wing blade. Glycosylation reactions demonstrated that PGANT3 glycosylates certain extracellular matrix (ECM) proteins. Immunoprecipitation experiments revealed that PGANT3 glycosylates tiggrin, an ECM protein known to bind integrin. We propose that this glycosyltransferase is uniquely responsible for glycosylating tiggrin in the wing disc, thus modulating proper cell adhesion through integrin-ECM interactions. This study provides the first evidence for the role of O-glycosylation in a developmentally regulated, integrin-mediated, cell adhesion event and reveals a novel player in wing blade formation during Drosophila development.